Respuesta :
Answer:
(-\infty,-1/2) U (1/2,+\infty)
Step-by-step explanation:
You have the following series:
[tex]\sum_{n=1}^{\infty} \frac{(2 x)^n}{n}[/tex]
You calculate the radius of convergence by using the formula:
[tex]R= \lim_{n \to \infty} |\frac{a(x)_n}{a(x)_{n+1}}|= \lim_{n \to \infty} |\frac{\frac{(2x)^n}{n}}{\frac{(2x)^{n+1}}{n+1}}|\\\\=\lim_{n \to \infty} |\frac{\frac{(2x)^n}{n}}{\frac{(2x)^n(2x)}{n+1}}|=\lim_{n \to \infty}|\frac{n+1}{2xn}|=|\frac{1}{2x}|\lim_{n \to \infty}|1+\frac{1}{n}|=|\frac{1}{2x}|[/tex]
The radius of convergence is R=1/2x.
Hence, the interval of convergence is
|2x| < 1
|x| < 1/2
By evaluating in the extrems of the interval:
[tex]\sum_{n=1}^{\infty} \frac{(2 (\frac{1}{2}))^n}{n}=\sum_{n=1}^{\infty} \frac{(1)^n}{n}=0\\\\\sum_{n=1}^{\infty} \frac{(2 (-\frac{1}{2}))^n}{n}=\sum_{n=1}^{\infty} \frac{(-1)^n}{n}[/tex]
for x=-1/2 we obtain an Alternating Harmonic Series, for x=1/2 we obtain the divergent harmonic series. Thus the interval is:
(-\infty,-1/2) U [1/2,+\infty)
Answer:
Step-by-step explanation:
Recall the ratio test. Given a series [tex]\sum_{n=1}^{\infty}a_n[/tex] if
[tex] \lim_{n\to \infty} \left|\frac{a_{n+1}}{a_n}\right|<1[/tex]
Then, the series is absolutely convergent.
We will use this to the given series [tex]\sum_{n=1}^{\infty} \frac{(2 x)^n}{n}[/tex], where [tex] a_n = \frac{(2 x)^n}{n}[/tex]. Then, we want to find the values for which the series converges.
So
[tex] \lim_{n\to \infty} \left|\frac{(2x)^{n+1}}{n+1}\cdot \frac{n}{(2x)^n}\right|<1[/tex], which gives us that
[tex] |2x|\cdot\lim_{n\to \infty} \frac{n}{n+1}<1[/tex]
We have that [tex]\lim_{n\to \infty} \frac{n}{n+1}=1[/tex]. Then, we have that
[tex]|2x|<1[/tex],
which implies that |x|<1/2. So for [tex]x \in (-1/2,1/2)[/tex] the series converges absolutely.
We will replace x by the endpoints to check convergence.
Case 1, x=1/2:
In this case we have the following series:
[tex]\sum_{n=1}^{\infty} \frac{1}{n}[/tex] which is the harmonic series, which is know to diverge.
Case 2, x=-1/2:
In this case we have the following series:
[tex]\sum_{n=1}^{\infty} \frac{(-1)^n}{n}[/tex]
This is an alternating series with [tex]b_n = \frac{1}{n}[/tex]. Recall the alternating series test. If we have the following
[tex]\sum_{n=1}^\infty (-1)^nb_n [/tex] and[tex] b_n[/tex] meets the following criteria : bn is positive, bn is a decreasing sequence and it tends to zero as n tends to infinity, then the series converge.
Note that in this case, [tex]b_n = \frac{1}{n}[/tex] si always positive, its' limit is zero as n tends to infinity and it is decreasing, hence the series converge.
So, the final interval of convergence is
[tex] [\frac{-1}{2}, \frac{1}{2})[/tex]